Transcriptome and metabolome profiling unveils the mechanisms of naphthalene acetic acid in promoting cordycepin synthesis in Cordyceps militaris - Wang, Xin; Li, Yin; Li, Xiue; Sun, Lei; Feng, Yetong; Sa, Fangping; Ge, Yupeng; Yang, Shude; Liu, Yu; Li, Weihuan; Cheng, Xianhao (Frontiers in Nutrition, 2023)
Cordycepin, an important active substance in Cordyceps militaris, possesses antiviral and other beneficial activities. In addition, it has been reported to effectively promote the comprehensive treatment of COVID-19 and thus has become a research hotspot. The addition of naphthalene acetic acid (NAA) is known to significantly improve the yield of cordycepin; however, its related molecular mechanism remains unclear. We conducted a preliminary study on C. militaris with different concentrations of NAA. We found that treatment with different concentrations of NAA inhibited the growth of C. militaris, and an increase in its concentration significantly improved the cordycepin content. In addition, we conducted a transcriptome and metabolomics association analysis on C. militaris treated with NAA to understand the relevant metabolic pathway of cordycepin synthesis under NAA treatment and elucidate the relevant regulatory network of cordycepin synthesis. Weighted gene co-expression network analysis (WGCNA), transcriptome, and metabolome association analysis revealed that genes and metabolites encoding cordycepin synthesis in the purine metabolic pathway varied significantly with the concentration of NAA. Finally, we proposed a metabolic pathway by analyzing the relationship between gene–gene and gene–metabolite regulatory networks, including the interaction of cordycepin synthesis key genes; key metabolites; purine metabolism; TCA cycle; pentose phosphate pathway; alanine, aspartate, and glutamate metabolism; and histidine metabolism. In addition, we found the ABC transporter pathway to be significantly enriched. The ABC transporters are known to transport numerous amino acids, such as L-glutamate, and participate in the amino acid metabolism that affects the synthesis of cordycepin. Altogether, multiple channels work together to double the cordycepin yield, thereby providing an important reference for the molecular network relationship between the transcription and metabolism of cordycepin synthesis.